Interstitial granulomatous dermatitis: rare cutaneous manifestation of rheumatoid arthritis - Isis Suga Veronez; Fernando Luiz Dantas; Neusa Yuriko Valente; Priscila Kakizaki; Thaís Helena Yasuda; Thaís do Amaral Cunha (Sociedade Brasileira de Dermatologia, 2015)
Abstract Besides being an uncommon clinicopathological entity, interstitial granulomatous dermatitis, also described as interstitial granulomatous dermatitis with arthritis (IGDA), has shown a wide spectrum of clinical manifestations, such as linear and erythematous lesions, papules, plaques and nodules. Histological features include dense dermal histiocytic infiltrate, usually in a palisade configuration, and scattered neutrophils and eosinophils. We describe a middle aged woman with rheumatoid arthritis of difficult management and cutaneous lesions compatible with IGDA.